American Medical Association complete guide to prevention and wellness : (Wiley, 2008)
Offering a guide to preventing illness and promoting health, experts from the American Medical Association introduce the foundations of life-long wellness, describing how to prevent such ailments as heart disease, stroke, cancer, hypertension, and diabetes.